Koneksi Analisis Riil dan Matematika Sekolah: Identifikasi pada Mahasiswa Calon Guru Matematika - Khamida Siti Nur Atiqoh; M Hafiz (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
There is a significant gap between secondary school mathematics and university mathematics courses. This study aims to identify how mathematics education students understand the connection between topics in Real Analysis and school mathematics content. The research method used in this study is a qualitative descriptive method with the research subjects being students who are pre-service mathematics teachers who are taking the Real Analysis course. Data analysis was carried out in 3 stages, namely: data condensation (data reduction), data presentation, and drawing conclusions. Concept-by-concept connections between Real Analysis topics and mathematics in secondary schools are categorized based on Suominen's categorization of mathematical connections. The research findings reveal that pre-service teachers have limitations in identifying the connections between Real Analysis and school mathematics topics. The connections that students identified were limited to general ideas. It is necessary to prepare a structured learning method in the Real Analysis course that can facilitate the gap between university mathematics and school mathematics.